Improving Antioxidant Effect of Stemona tuberosa by Fermentation with Endophytic Fungus Penicillium expansum STRB13 - Dong, Jian-Wei; Li, Xue-Jiao; Zhao, Hui; Wang, Xue-Xian (Natural Products Journal, The, 2026)
BackgroundStemona tuberosa Lour. is a plant belonging to the genus Stemona (Stemonaceae) that has been utilized in traditional Chinese medicine (TCM) for its antitussive and antiparasitic properties. Endophytic fungi have been shown to play an important role in the growth and metabolism of plants. Fermentation involving endophytic fungi tends to result in the production of new or more potent pharmacological compounds.ObjectiveThe study aims to enhance the antioxidant activity of S. tuberosa by fermenting it with a symbiotic endophytic fungus.MethodsSeven symbiotic endophytic fungi were used to screen and ferment S. tuberosa to improve antioxidant activity estimated by 2,2’-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and ferric ion-reducing antioxidant power (FRAP). The chemical constituent changes were characterized by ultraviolet (UV) spectrum and high-performance liquid chromatography (HPLC) analysis.Results and DiscussionPenicillium expansum STRB13, an endophytic fungus associated with S. tuberosa, was screened for its ability to enhance antioxidant capacity through fermentation. The fermentation of S. tuberosa using P. expansum STRB13 significantly improved its DPPH radical scavenging activity, achieving an IC50 value of 24.2 μg/mL. Additionally, the ferric reducing antioxidant power (FRAP) of the fermented sample was fourteen times greater, measuring 388.1 ± 32.6 μmol/L compared to 27.5 ± 1.0 μmol/L in the blank sample. Differences observed between the blank and P. expansum STRB13 fermented S. tuberosa (FST) in UV spectra and HPLC analysis indicated the production of new aromatic phenolic compounds through fermentation, which contributed to the enhanced antioxidant activity.ConclusionThis is the first time reporting on the fermentation processing of S. tuberosa with symbiotic endophytic fungus. This study revealed that P. expansum STRB13 FST will be an alternative natural antioxidant. Fermentation with symbiotic endophytic fungus is a new approach to processing TCM and discovering new compounds.
Keywords: Stemona tuberosa